Towards Enabling Service-Oriented Architecture Implementation Initiative - Sulong, Muhammad Suhaizan; Koronios, Andy; Gao, Jing; Abdul-Aziz, Azlianor (2011)
Service-oriented architecture (SOA) is claimed to be more than just technology which link information technology capabilities and business needs. It offers a new way of thinking about how organisations manage and implement information technology within and between organisations and systems in order to make business more flexible and agile. This means organisations that want to deliver the most comprehensive solutions for solving business issues and problems, should have SOA implementation initiatives in which the organisations need to consider the importance of SOA initiative compare to information system adoption, the process of implementing SOA initiative and the factors to assist the SOA initiative journey. This paper provides the insight from literature of what organisations would consider having SOA initiatives and might be beneficial for their business agility and flexibility to pursue with their SOA initiatives. This study will further develop a framework for building better SOA solutions through conducting case studies.